2006
DOI: 10.1007/s11224-006-9047-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Gaussian-3X theory for chlorinated organic molecules. Enthalpies of formation of chlorobenzenes and predictions for polychlorinated aromatic compounds

Abstract: The enthalpies of formation of chlorinated methanes, ethanes, ethylenes, phenols, and benzenes have been calculated at the G3X level of theory using the atomization energy procedure and the method of isodesmic reactions. By comparing the most reliable experimental data on chlorinated hydrocarbons recommended by Manion [Manion JA (2002) J Phys Chem Ref Data 31:123] with the G3X results, the accuracy of theoretical enthalpies of formation is estimated as ranging from ± 4 to ± 10 kJ/mol. Only for hexachloroethane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 18 publications
(41 reference statements)
0
16
0
Order By: Relevance
“…The values are still much higher than the experiments as indicated in Table 3. Dorofeeva et al, 48 however, insisted on the experimental values from the agreement on the enthalpy changes of the following reactions from experiments and G3X, arguing that these reactions are better balanced on the Cl-Cl interactions: 62 and for C 6 H 3 Cl 3 from Yan et al 27 Agreement within 7 kJ/mol is observed across different isodesmic reactions (Table 3). In these isodesmic reactions, nonspecified C 6 H 4 Cl Judging from the standard deviation of the average over different isodesmic reactions, the propagation of errors from C 6 H 6-n Cl n (n ) 0-3), and the accuracy of G3X on the enthalpy changes of reactions, an approximate confidence range of (5 kJ/mol is assigned to current G3X enthalpies of formation for C 6 H 2 Cl 4 , C 6 HCl 5 and C 6 Cl 6 using isodesmic reactions.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The values are still much higher than the experiments as indicated in Table 3. Dorofeeva et al, 48 however, insisted on the experimental values from the agreement on the enthalpy changes of the following reactions from experiments and G3X, arguing that these reactions are better balanced on the Cl-Cl interactions: 62 and for C 6 H 3 Cl 3 from Yan et al 27 Agreement within 7 kJ/mol is observed across different isodesmic reactions (Table 3). In these isodesmic reactions, nonspecified C 6 H 4 Cl Judging from the standard deviation of the average over different isodesmic reactions, the propagation of errors from C 6 H 6-n Cl n (n ) 0-3), and the accuracy of G3X on the enthalpy changes of reactions, an approximate confidence range of (5 kJ/mol is assigned to current G3X enthalpies of formation for C 6 H 2 Cl 4 , C 6 HCl 5 and C 6 Cl 6 using isodesmic reactions.…”
Section: Resultsmentioning
confidence: 98%
“…21,[29][30][31][32][33] The results often carry large uncertainties, and the agreement between different measurements, if they exist, is poor, e.g., ∆ f H 298K °(g, 1,2,4-C 6 H 3 Cl 3 ) from two groups differ by as much as 13 kJ/mol. 25,27 Alternately, predictions of the enthalpies of formation of these compounds have used the group additivity method, [34][35][36][37] semiempirical PM3 11,38 and MNDO, 39,40 density functional theory (DFT) methods, 12,[41][42][43][44][45][46][47] and recently G3X calculations on ClBzs 44,48 and G3MP2 on several phenols and phenoxy radicals. 49 DFT and ab initio predictions are often coupled with isodesmic reactions to gain better reliability, and close agreement with the experimental and compiled values has been obtained for Di-ClBzs 12,41,44 and Di-ClPhs.…”
Section: Introductionmentioning
confidence: 99%
“…For urea, the D f H m values calculated from reactions (1) and (2) agree well with the G3X result, whereas a large discrepancy is observed for reactions (3) and (4). This discrepancy may be a result of worse group balance in these reactions compared to reactions (1) and (2), as well as insufficient accuracy of the experimental D f H m value of formamide, especially taking into account that two these molecules present in reaction (3). Note, that the result from isodesmic reaction (4) is in good agreement with the value of enthalpy of formation of urea (À245.8 kJ Á mol À1 [12]) based on the underestimated value of enthalpy of sublimation.…”
Section: Reactionmentioning
confidence: 99%
“…For the 222 enthalpies of formation of small and moderate sized molecules with 2 to 10 non-hydrogen atoms, one of the latest version, Gaussian-3X (G3X) theory, achieves the so-called thermochemical accuracy of about 4 kJ Á mol À1 [2]. Recently we have assessed the capability of the G3X method for chlorinated and organophosphorus compounds with up to 12 non-hydrogen atoms [3,4]. It was shown that the G3X method is able to predict sufficiently accurate values of enthalpies of formation of these compounds and can be used for detecting anomalies in reported enthalpies of formation.…”
Section: Introductionmentioning
confidence: 99%
“…As the enthalpies of formation of organic compounds are often subjected to considerable uncertainties Dorofeeva, Vishnevskiy, and Moiseeva [213] in the next paper calculated reactions the enthalpies of formation of chlorinated methanes, ethanes, ethylenes, phenols, and benzenes using the atomization energy procedure and isodesmic reactions. Theoretical enthalpies of formation were compared with experimental data [214].…”
Section: Issuementioning
confidence: 99%